Integrative or Complementary? ?Archeology? of Polish General Pedagogy Transformations in the Twentieth Century - Stępkowski, Dariusz (INSTED: Interdisciplinary Studies in Education & Society, 2020)
This text analyzes a difference between the complementary and integrative form of exploring general pedagogy in Poland in the 20th century. The Polish term ?kształcenie? creates a space for this analysis. By using Foucault?s archeological method and a concept of Koselleck?s time layers, the author investigates the changes in interpreting the word ?kształcenie? and its domain assignment. The author will conduct a detailed analysis of the socialist totalitarianism during which pedagogical thinking was converted to a politically deformed educational thinking.